Modeling Niemann-Pick disease type C1 in zebrafish: a robust platform for in vivo screening of candidate therapeutic compounds - Wei-Chia Tseng; Hannah E. Loeb; Wuhong Pei; Chon-Hw; Lisha Xu; Celine V. Cluzeau; Christopher A. Wassif; Benjamin Feldman; Shawn M. Burgess; William J. Pavan; Forbes D. Porter (The Company of Biologists, 2018)
Niemann-Pick disease type C1 (NPC1) is a rare autosomal recessive lysosomal storage disease primarily caused by mutations in NPC1. NPC1 is characterized by abnormal accumulation of unesterified cholesterol and glycolipids in late endosomes and lysosomes. Common signs include neonatal jaundice, hepatosplenomegaly, cerebellar ataxia, seizures and cognitive decline. Both mouse and feline models of NPC1 mimic the disease progression in humans and have been used in preclinical studies of 2-hydroxypropyl-β-cyclodextrin (2HPβCD; VTS-270), a drug that appeared to slow neurological progression in a Phase 1/2 clinical trial. However, there remains a need to identify additional therapeutic agents. High-throughput drug screens have been useful in identifying potential therapeutic compounds; however, current preclinical testing is time and labor intensive. Thus, development of a high-capacity in vivo platform suitable for screening candidate drugs/compounds would be valuable for compound optimization and prioritizing subsequent in vivo testing. Here, we generated and characterize two zebrafish npc1-null mutants using CRISPR/Cas9-mediated gene targeting. The npc1 mutants model both the early liver and later neurological disease phenotypes of NPC1. LysoTracker staining of npc1 mutant larvae was notable for intense staining of lateral line neuromasts, thus providing a robust in vivo screen for lysosomal storage. As a proof of principle, we were able to show that treatment of the npc1 mutant larvae with 2HPβCD significantly reduced neuromast LysoTracker staining. These data demonstrate the potential value of using this zebrafish NPC1 model for efficient and rapid in vivo optimization and screening of potential therapeutic compounds. This article has an associated First Person interview with the first author of the paper.